Insights into Molecular Mechanism of Secondary Xylem Rapid Growth in Salix psammophila - Hongxia Qiao; Yunhan Wang; Lin Shi; Ruiping Wang; Yeru Yang; Dongshan Wei; Yingjie Li; Kairui Chao; Li Jia; Guiming Liu; Fengqiang Yu; Jiewei Zhang; et al. (Plants)
Salix psammophila C. Wang & C. Y. Yang is an important windbreak and sand-fixing shrub species in Northwest China, with excellent characteristics such as resistance to drought, wind, and sand. S. psammophila needs to be stubbed flat after several years of growth to continue to grow, otherwise, its growth rate will slow down and even begin to die. To understand the genetic regulatory mechanism of secondary growth in S. psammophila, cell structure and transcriptome analysis were performed on the secondary xylem and secondary phloem of stems. The results showed that the secondary xylem and the secondary phloem of S. psammophila were well developed at 1, 2, and 3-year-old stages, and the secondary growth changes mainly occurred in the secondary xylem at the 2 to 3-year-old stage, with a faster growth rate. The CSE2 and CSE1 genes that regulate CSE (caffeoyl shikimate esterase) have high sequence similarity (92% and 93%) with the CSE2 and CSE1 genes of the genus Populus, respectively, and regulate lignin biosynthesis. Notably, the expression levels of these two genes decreased in the secondary xylem of 3-year-old S. psammophila, indicating that the rapid growth of S. psammophila may be related to lignin biosynthesis. Weighted gene co-expression network analysis (WGCNA) was utilized to screen candidate TFs and genes involved in the secondary growth processes of S. psammophila, which were categorized into six co-expression modules. A total of 79 genes were selected from these co-expression modules, and co-expression network maps of the genes were constructed. The results indicate that the secondary growth of S. psammophila was regulated by a TF regulatory network. Interestingly, PLATZ TFs were involved in the rapid secondary growth and stress tolerance in S. psammophila. This hints that S. psammophila may promote secondary growth by increasing stress tolerance.